Anticancer potential of allicin: A review. (March 2022) - Catanzaro, Elena; Canistro, Donatella; Pellicioni, Valentina; Vivarelli, Fabio; Fimognari, Carmela
Abstract: Phytochemicals have attracted attention in the oncological field because they are biologically friendly and have relevant pharmacological activities. Thanks to the intense and unique spicy aroma, garlic is one of the most used plants for cooking. Its consumption is correlated to health beneficial effects towards several chronic diseases, such as cancer, mainly attributable to allicin, a bioactive sulfur compound stored in different plant parts in a precursor form. The objective of this review is to present and critically discuss the chemistry and biosynthesis of allicin, its pharmacokinetic profile, its anticancer mechanisms and molecular targets, and its selectivity towards tumor cells. The research carried out so far revealed that allicin suppresses the growth of different types of tumors. In particular, it targets many signaling pathways associated with cancer development. Future research directions are also outlined to further characterize this promising natural product. Graphical Abstract: ga1